Review of Susan Westhafer Furukawa’s The Afterlife of Toyotomi Hideyoshi: Historical Fiction and Popular Culture in Japan - Scott Mehl (The ASIANetwork Exchange: A Journal for Asian Studies in the Liberal Arts, 2023)
Susan Westhafer Furukawa’s The Afterlife of Toyotomi Hideyoshi: Historical Fiction and Popular Culture in Japan (Harvard University Press, 2022) is an engagingly written study of twentieth- and twenty-first-century representations of a crucial figure in Japanese history. The research is thorough; the critical underpinnings of the study are accessibly presented; the illustrations, which grace nearly every chapter,serve to enhance what is already a valuable addition to any library that is staying abreast of significant developments in Japanese literary and historical scholarship.